Identification of QTLs controlling aroma volatiles using a ‘Fortune’ x ‘Murcott’ (Citrus reticulata) population - Yu, Yuan (BMC Genomics, 2017)
BACKGROUND: Flavor is an important attribute of mandarin (Citrus reticulata Blanco), but flavor improvement via conventional breeding is very challenging largely due to the complexity of the flavor components and traits. Many aroma associated volatiles of citrus fruit have been identified, which are directly related to flavor, but knowledge of genetic linkages and relevant genes for these volatiles, along with applicable markers potentially for expeditious and economical marker-assisted selection (MAS), is very limited. The objective of this project was to identify single nucleotide polymorphism (SNP) markers associated with these volatile traits. RESULT: Aroma volatiles were investigated in two mandarin parents (‘Fortune’ and ‘Murcott’) and their 116 F(1) progeny using gas chromatography mass spectrometry in 2012 and 2013. A total of 148 volatiles were detected, including one acid, 12 alcohols, 20 aldehydes, 14 esters, one furan, three aromatic hydrocarbons, 16 ketones, one phenol, 27 sesquiterpenes, 15 monoterpenes, and 38 unknowns. A total of 206 quantitative trait loci (QTLs) were identified for 94 volatile compounds using genotyping data generated from a 1536-SNP Illumina GoldenGate assay. In detail, 25 of the QTLs were consistent over more than two harvest times. Forty-one QTLs were identified for 17 aroma active compounds that included 18 sesquiterpenes and were mapped onto four genomic regions. Fifty QTLs were for 14 monoterpenes and mapped onto five genomic regions. Candidate genes for some QTLs were also identified. A QTL interval for monoterpenes and sesquiterpenes on linkage group 2 contained four genes: geranyl diphosphate synthase 1, terpene synthase 3, terpene synthase 4, and terpene synthase 14. CONCLUSIONS: Some fruit aroma QTLs were identified and the candidate genes in the terpenoid biosynthetic pathway were found within the QTL intervals. These QTLs could lead to an efficient and feasible MAS approach to mandarin flavor improvement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-4043-5) contains supplementary material, which is available to authorized users.